2019
DOI: 10.1017/s0950268818003473
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia hospitalisation and case-fatality rates in older Australians with and without risk factors for pneumococcal disease: implications for vaccine policy

Abstract: Community-acquired pneumonia (CAP) results in substantial numbers of hospitalisations and deaths in older adults. There are known lifestyle and medical risk factors for pneumococcal disease but the magnitude of the additional risk is not well quantified in Australia. We used a large population-based prospective cohort study of older adults in the state of New South Wales (45 and Up Study) linked to cause-specific hospitalisations, disease notifications and death registrations from 2006 to 2015. We estimated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…First, this indicates that bacterial testing is often not performed in-hospital, as previously reported [ 14 ]. Second, it highlights the need for preventive strategies as noted in recent studies, which stress the use of pneumococcal vaccination in older individuals and in those with risk factors such as chronic obstructive pulmonary disease, male gender, and diabetes [ 15 , 16 ]. Third, the lack of an etiologic diagnosis may increase the risk of overuse, inappropriate, or inefficient antimicrobial therapy and, ultimately, the selection of resistant and multi-drug resistant bacteria [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, this indicates that bacterial testing is often not performed in-hospital, as previously reported [ 14 ]. Second, it highlights the need for preventive strategies as noted in recent studies, which stress the use of pneumococcal vaccination in older individuals and in those with risk factors such as chronic obstructive pulmonary disease, male gender, and diabetes [ 15 , 16 ]. Third, the lack of an etiologic diagnosis may increase the risk of overuse, inappropriate, or inefficient antimicrobial therapy and, ultimately, the selection of resistant and multi-drug resistant bacteria [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Germany, the mean age was 76 for hospitalized patients [23]. Another study conducted in Australia found the rate of hospitalizations as 563 per 100,000 in the 65 to 74 age group [24]. In our study, the mean age of the patients who were discharged was 67.17, the mean age of the patients who were hospitalized in the service was 70.85 and the mean age of the patients who were admitted to the intensive care unit was 77.68.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae is reportedly responsible for 30–38% of community-acquired pneumonia ( Johansson et al, 2010 ; Holter et al, 2015 ). Hospital-acquired pneumonia is among the most frequent nosocomial infections, and is associated with prolonged hospital stay and high costs ( Guidelines for the manage, 2005 ), and the case fatality rate increases in line with increasing age ( Dirmesropian et al, 2019 ). Streptococcus pneumoniae is spread by coughing, sneezing and respiratory secretions, and up to 50% of children may be asymptomatic carriers ( Hussain et al, 2005 ), although carriage rates decrease to around 10% in adulthood ( Goldblatt et al, 2005 ), and even lower in elderly individuals ( Ridda et al, 2010 ).…”
Section: Routine Vaccination and Travelmentioning
confidence: 99%